2015
DOI: 10.1177/1555412015605219
|View full text |Cite
|
Sign up to set email alerts
|

Flow Experience of Older Adults Using the iStoppFalls Exergame

Abstract: Knowledge about the experiences of flow by older adults through the engagement of digital games is scarce. This article describes an important element of an international, multicenter, randomized, controlled trial which utilized three purpose-built exergames to facilitate physical activity and to assist with fall prevention of adults aged 65þ years in their homes. Measurement of flow was assessed through the distribution of the Activity Flow State Scale in participants assigned to the intervention group after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 31 publications
0
16
0
4
Order By: Relevance
“…These challenges might be particularly engaging (Csikszentmihalyi 1990;Kivikangas 2006;Marston et al 2016). The player is required to participate in order for the game to proceed (blinded for review, in press).…”
Section: Meaningfulness and Video Gamesmentioning
confidence: 99%
“…These challenges might be particularly engaging (Csikszentmihalyi 1990;Kivikangas 2006;Marston et al 2016). The player is required to participate in order for the game to proceed (blinded for review, in press).…”
Section: Meaningfulness and Video Gamesmentioning
confidence: 99%
“…Conversely, citizens have bored witness to the rise and development of mobile phones, with many using and owning smartphones offering the user a vast has in turn led to the development of mobile apps (mApps) and mobile health (mHealth) apps, which facilitate people to self-monitor their health and share their data with their friends and health practitioner. 51 Whilst videogames have garnered great interest and worldwide investigations, focusing on the use of health and societal benefits, [52][53][54][55][56] little focus has explored how videogames could be integrated into an age-friendly city. This seems to be true for the whole spectrum of technological solutions that are available on the marketplace to support older people.…”
Section: Discussionmentioning
confidence: 99%
“…A notable aspect to highlight within related literature because it relates to game adherence among participants is the experience of flow and immersion [19][20][21][22][23]. Research in this area among older adult populations is still in its infancy, yet has been growing with work undertaken by Marston [24][25] and Whitelock [26]. Although research in this domain of game studies has explored younger generations, such as men in their twenties playing first-person shooter games, no study has been identified that examines the effects of flow/immersion by nongamers from Gen X.…”
Section: Recent Studies: Today's Older Adults and Digital Gamesmentioning
confidence: 99%